2018
DOI: 10.1002/app.46376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polypropylene/polystyrene boehmite alumina nanocomposites: Impact of filler surface modification on the mechanical, thermal, and rheological properties

Abstract: The influences of surface treatment and the concentration of boehmite alumina (BA) particles on polypropylene and polystyrene (PS) (80/20) blends produced via melt compounding were examined. The results show that p‐toluene sulfonic acid‐treated BA particles yielded the highest stiffness improvement (27.5%), followed by untreated particles (25.7%), and dodecylbenzene sulfonic acid‐treated BA particles (8.5%). Transmission electron microscopy revealed that p‐toluene sulfonic acid‐treated BA particle agglomerates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…As a result of previous research, there has been a fast growth in the production of ceramic‐based polymer matrix composites. Examples of such composites are SiO 2 ‐poly(ethylene glycol) (PEG)‐3‐isocyanate‐propyltrietoxysilane, silica–polymer system, poly(vinyl alcohol)–Fe 3 O 4, and Al 2 O 3 –polymer matrix . However, the above applications imperatively require a thorough knowledge of how external forces and temperature affect the behavior of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of previous research, there has been a fast growth in the production of ceramic‐based polymer matrix composites. Examples of such composites are SiO 2 ‐poly(ethylene glycol) (PEG)‐3‐isocyanate‐propyltrietoxysilane, silica–polymer system, poly(vinyl alcohol)–Fe 3 O 4, and Al 2 O 3 –polymer matrix . However, the above applications imperatively require a thorough knowledge of how external forces and temperature affect the behavior of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…The fillers that have been widely used for reinforcement purpose are organic fillers, ZnO, kaolin, CaCO 3 (CC), rice husk ash (RHA), etc. CC is one of the most commonly used inorganic fillers in thermoplastics such as poly(vinyl chloride) and PP .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are ways of improving the properties of PLA, including the addition of fillers or blending with other polymers [3,[7][8][9][10]. For instance, Nieddu et al [11] reported that 5 wt.% nanoclay increased the modulus of neat PLA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nieddu et al [11] reported that 5 wt.% nanoclay increased the modulus of neat PLA. Other fillers, such as nano-silicon dioxide (SiO 2 ) [12] and boehmite (BA) [10], have been found to improve the thermal stability, crystallizability, and mechanical and electrical conductivity of the polymers. Amongst these, BA has attracted more research interest due to its low cost, high flammability, high surface area, noble dispensability, and thermal stability [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation